The Effectiveness of Individual Counseling with the Reflection of Feeling Technique to Improve Self-Awareness and Self-Esteem - Ummi Qudsiyah; Akhmad Dasuki (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Self- awareness and self- esteem are important aspects of psychological well-being, yet many students show low levels of self- awareness and self-esteem, which can hinder their personal development. Aim: This study aims to analyze the effectiveness of the reflection of feeling counseling technique in enhancing self-awareness and self-esteem among students. Method: The research uses an experimental method with a Single Subject Design (SSD) type A-B-A, where the baseline phase is conducted before and after the intervention across five sessions, while the intervention phase is carried out over eight counseling sessions. The research subjects are fifth-semester students from the Islamic Guidance and Counseling (BKI) program at IAIN Palangkaraya, selected through purposive sampling. Measurements are conducted using the adapted Situational Self Awareness Scale and Private Self-Consciousness Scale for self-awareness, as well as the Coopersmith Self-Esteem Inventory (CSEI) for self-esteem. Results and Dıscussion: The results of the study show a significant increase in self-esteem by 75.3% and self-awareness by 70.3% from the initial condition. The reflection of feeling technique proved effective in enhancing self-understanding and positive self-assessment among the participants. The stability of changes in the final phase indicates that this intervention has a positive long-term impact. Conclusion: This study concludes that the reflection of feeling technique can be an effective strategy for developing self-esteem and self-awareness in the context of individual counseling.